(untitled) (Quinto Sol, 2025)
The relationship between road infrastructure and tourism practices is undeniable. Mendoza, an Argentine province located at the foot of the Andes, was early on a transit point for travelers, both local and foreign. This article analyzes the changes that occurred in mountain tourism practices in Mendoza during the period 1900-1930, based on the relationship between the widespread use of mechanized transport and the expansion and improvement of existing roads, as well as the construction of new ones. The development of the road network played a fundamental role, highlighting not only the influence of public policies at the time, but also the way in which hegemonic discourses echoed the current modernization process. The review of primary sources, such as newspaper articles, legislative session journals, travel guides, statistical yearbooks, photographs and plans, and reports from the Ministry of Industry and Public Works, allowed us to reconstruct the discussions surrounding the topic from a historical perspective, through discursive and photographic analysis.